Legal Protection For Consumers Of Product Warranty In Business Law - Posumah, Natalia (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
In article 30 of Law No. 8 of 1999 concerning Consumer Protection expressly regulates the authority to supervise business actors carried out by the government, the community, and the Non- Governmental Consumer Protection Institute (LPMSM), but the facts on the ground consumers still get product guarantees from business actors that are not in accordance with Law No .8 of 1999 concerning Consumer Protection. This shows that there has been an imbalance between regulations and facts on the ground. The problem in this study is how consumer protection against product warranties in business law and what are the consequences of warranties that are not in accordance with Law No. 8 of 1999 concerning Consumer Protection. This research method uses a normative juridical approach, with secondary data collection, to prove the consequences of guarantees that are not in accordance with Law No. 8 of 1999 concerning Consumer Protection. The data obtained were analyzed qualitatively. Based on the results of the study it was found that many losses experienced by consumers related to guarantees, such as fraud against store guarantees, fraud against bank guarantees, and others. Therefore, the government provides guarantees for the protection of consumers against product warranties through government regulations, one of which is the UUPK. In its implementation, consumer protection has not been carried out to the fullest, this is proven because there are still many irregularities and losses felt by the government. Whereas in the UUPK the sanctions/consequences received by the business actor if committing a violation related to goods will be subject to criminal acts.